Polychaeta-mediated synthesis of gold nanoparticles: A potential antibacterial agent against Acute Hepatopancreatic Necrosis Disease (AHPND)–causing bacteria, Vibrio parahaemolyticus. - Mohamad Sofi Abu Hassan; Nurul Ashikin Elias; Marina Hassan; Sharifah Rahmah; Wan Iryani Wan Ismail; Noor Aniza Harun (Heliyon, 2023)
Gold nanoparticles (AuNPs) have emerged as a promising application in aquaculture. Their nano-sized dimensions, comparable to pathogens offer potential solutions for combating antibiotic resistance. In this study, AuNPs were synthesized by using polychaetes, Marphysa moribidii as the bio-reducing agent. Modifications were made to reduce agglomeration in green-synthesized AuNPs through ultrasonication. The antibacterial activities of AuNPs against V. parahaemolyticus were evaluated. The physicochemical characteristics of the green synthesized AuNPs were comprehensively investigated. The successful formation of AuNPs was confirmed by the appearance of a red ruby colour and the presence of surface Plasmon resonance (SPR) absorption peaks at 530 nm as observed from UV–vis spectroscopy. Scanning electron microscopy (SEM) revealed spherical-shaped AuNPs with some agglomerations. Transmission electron microscopy (TEM) showed particle size of AuNPs ranging from 10 nm to 60 nm, meanwhile dynamic light scattering (DLS) analysis indicated an average particle size of 24.36 nm. X-ray diffraction (XRD) analysis confirmed the high crystallinity of AuNPs, and no AuNPs were detected in the polychaetes extracts prior to synthesis. A brief ultrasonication significantly reduced the tendencies for AuNPs to coalesce. The green-synthesized AuNPs demonstrated a remarkable antibacterial efficacy against V. parahaemolyticus. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) tests revealed that a concentration of 0.3 g/ml of AuNPs effectively inhibited V. parahaemolyticus. These findings highlighted the potential of green-synthesized AuNPs as antibacterial agents for the prevention and management of AHPND in aquaculture.